VD_FINDINFO AP / 2011 / 95 vom 13. April 2011 - VD Tribunal cantonal (2011)
LÉGITIMATION ACTIVE ET PASSIVE, DÉCISION PRÉJUDICIELLE | 285 CPC, 339a al. 4 CPC, 339b al. 2 CPC, 452 al. 1ter CPC, 452 al. 2 CPC, 452 CPC